DYNAMICS OF MORTALITY RATE DUE TO CIRCULATORY DISEASES IN THE KEMEROVO REGION IN THE PERIOD 2006 - 2014 - Наталья Владимировна Кондрикова; Ирина Владимировна Самородская; Ольга Леонидовна Барбараш (Медицина в Кузбассе)
Objective – to identify the changes of mortality rates due to circulatory diseases in the Kemerovo region during the period from 2006 to 2014 in a comparative analysis with the data in the Russian Federation. There are following tasks: to study the dynamics of mortality rates in the Kemerovo region due to circulatory diseases from 2006 to 2014; to evaluate the changes in the nosological structure of causes of death in the class of circulatory diseases, occurred in the period from 2006 to 2014; to compare the analyzed mortality rates in the Kemerovo region with all-Russian rates.